Ovarian cancer: New therapies, potential risk factors and prognostic values for improving survival outcomes in women - Chuffa, Luiz Gustavo de Almeida [UNESP]; Ferreira Seiva, Fábio Rodrigues; de Arruda Amorim, João Paulo; Lupi Júnior, Luiz Antonio [UNESP] (My University, 2015)
Ovarian cancer (OC) is the third most diagnosed gynecologic cancer and the first leading cause of death from all of gynecological malignancies. OC presents with the highest mortality rate, largely due to its advanced stage at the time of diagnosis. About 90% of these cases are epithelial ovarian cancer (EOC), and 70% are diagnosed with widespread intra-abdominal or distant metastases. Unfortunately, the frequency of invasive and advanced EOC is mostly due to the lack of a suitable and sufficiently reliable screening tool at the moment of diagnosis. Despite new strategies and improvements in surgical techniques and chemotherapeutic options, a 5-year survival rate for invasive EOC is approximately 46%. The main symptoms reported from OC include abnormal vaginal bleeding, pelvic and abdominal pain, weight loss, back pain, urinary urgency, and fatigue, which contribute to the difficulties of an early diagnosis, thereby resulting in low prognosis and survival rates. The treatment of early stage OC involves surgical resection followed by chemotherapy; clinical trials show an overall survival rate with adjuvant platinum-based chemotherapy, but this treatment in sub-groups of patients may vary according to different prognosis. Many risk factors associated with breast cancer are also related to the risk of other gynecologic cancers, such as OC. They include current age, age at menarche, parity, and first-degree family history with a wide interindividual genetic variations in the susceptibility of OC. Recent studies regarding genome-wide association have reported several single nucleotide polymorphisms that confer low-penetrance susceptibility to EOC. In addition, mutations in BRCA gene, the gene that produces breast cancer-linked protein, are strongly associated with hereditary forms of OC. Hormone replacement therapy is further associated with increased risks of OC, mainly long duration use of both unopposed estrogens and estrogens plus progestins, regardless of treatment regimen. Independent prognostic factors are often considered including those described by International Federation of Gynecology and Obstetrics (FIGO), such as stage, tumor grade, volume of residual OC, and specific biomarkers for predicting survival in ovarian tumor patients. This chapter will discuss the new therapies, major risk factors in early and advanced ovarian cancer stage, and most prognostic factors as a tool for improving the survival rate outcomes in women.